Immersion immunization with recombinant Saccharomyces cerevisiae displaying ORF25 induced protective immunity against cyprinid herpesvirus 2 - Yang, Maoxia (Journal of fish diseases, 2024)
© 2024 John Wiley & Sons Ltd.